1990
DOI: 10.1148/radiology.175.2.2326479
|View full text |Cite
|
Sign up to set email alerts
|

Spinal bone mineral density measured with quantitative CT: effect of region of interest, vertebral level, and technique.

Abstract: This study documents the relationship between different vertebral bone compartments with quantitative computed tomography (CT). Four distinct patient groups were investigated: healthy pre- and early postmenopausal women as well as healthy and osteoporotic late postmenopausal women. Three different regions of interest (ROIs) were employed: the elliptical ROI located in the anterior trabecular portion of the vertebral body, the peeled ROI of irregular shape that circumscribes most of the trabecular bone, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
57
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(69 citation statements)
references
References 0 publications
10
57
0
2
Order By: Relevance
“…The error in precision has been estimated at 2% for bone mineral density in the proximal femur, 4% and 5% in the distal femur and proximal tibia and 3% for muscle volume in the mid-femur. These estimates were made in our department with the same equipment (Neander et al 1997a), and are similar to those reported elsewhere (Steiger et al 1990, Karantanas et al 1991.…”
Section: Methodssupporting
confidence: 85%
“…The error in precision has been estimated at 2% for bone mineral density in the proximal femur, 4% and 5% in the distal femur and proximal tibia and 3% for muscle volume in the mid-femur. These estimates were made in our department with the same equipment (Neander et al 1997a), and are similar to those reported elsewhere (Steiger et al 1990, Karantanas et al 1991.…”
Section: Methodssupporting
confidence: 85%
“…The precision error has earlier been estimated at 2% for bone mineral density in the middle femur, 4% and 5% of the distal femur and the proximal tibia, respectively, and 3% for muscle volume of the the middle femur in our department with the same equipment (Neander et al 1997). These values are similar to those that others have found (Steiger et al 1990, Karantanas et al 1991.…”
Section: Methodssupporting
confidence: 92%
“…Moreover, standard spinal DXA scans are influenced by also by the posterior portions of the vertebrae and not directly visible. Spinal QCT are superior in detecting true bone loss (34) with comparative studies indicating a progressive bone loss in the anterior vertebral body portions rich in trabecular bone and not detected by DXA (35)(36)(37). Nevertheless, DXA is currently the mainstay in terms of clinical utility which warrants improved understanding on how to interpret the findings, particularly in the aged.…”
Section: Discussionmentioning
confidence: 99%